Nanomaterials based on thermosensitive polymer in biomedical field - Guo, Yingshu; Sun, Li; Wang, Yajing; Wang, Qianqian; Jing, Dan; Liu, Shiwei (Frontiers in Chemistry, 2022)
The progress of nanotechnology enables us to make use of the special properties of materials on the nanoscale and open up many new fields of biomedical research. Among them, thermosensitive nanomaterials stand out in many biomedical fields because of their “intelligent” behavior in response to temperature changes. However, this article mainly reviews the research progress of thermosensitive nanomaterials, which are popular in biomedical applications in recent years. Here, we simply classify the thermally responsive nanomaterials according to the types of polymers, focusing on the mechanisms of action and their advantages and potential. Finally, we deeply investigate the applications of thermosensitive nanomaterials in drug delivery, tissue engineering, sensing analysis, cell culture, 3D printing, and other fields and probe the current challenges and future development prospects of thermosensitive nanomaterials.